Simulation and refraction event of complex hyperbolic type solitary wave in plasma and optical fiber for the perturbed Chen-Lee-Liu equation - Yokus, Asif; Durur, Huelya; Duran, Serbay (Springer, 2021)
In this article, Modified 1/G '-expansion and Modified Kudryashov methods are applied to generate traveling wave solutions of Perturbed Chen-Lee-Liu equation. The similar and different aspects of the solutions produced by both analytical methods are discussed. By giving special values to the constants in the solutions obtained by analytical methods, 2D, 3D and contour graphics representing the shape of the standing wave at any time are presented. Additionally, the advantages and disadvantages of the two analytical methods are discussed and presented. Also, a solitary wave is produced by giving special values to the parameters in the hyperbolic type complex traveling wave solution. Simulations are created for different values of the amplitute and velocity propagation parameters of the solitary wave. The values of these parameters are calculated for the breakage event physically. A computer package program is used for operations such as solving complex operations, drawing graphics and solving systems of algebraic equations.
Keywords: The Modified 1/G'-expansion method; Modified Kudryashov method; The Perturbed Chen-Lee-Liu equation; Traveling wave solution